Greek mythological horses and the world's boundary - Milićević Bradač, Marina (Array, 2003)
Greek mythological horses, like Arion, Pegasus, Xanthus, Skyphius and others, show directa and indirect connection with water of any kind. This particular connection between horses and water would not stem from the notions of vegetation and fertility, but from the idea that water is the border between the world of the living and the Otherworld. The horse was psychopompos who carried the soul of the deceased across the border, and he also carried the shaman during his ecstatic journey.